FIGURATIONS OF MASCULINITY IN THE WILD PALMS, BY WILLIAM FAULKNER - Silva, Claudimar Pereira da [UNESP]; Valentim, Jorge Vicente (Univ Federal Juiz Fora, Campus Univ, 2020)
This article aims to analyze the representations of masculinities in the narrative The wild palms, by William Faulkner, which integrates the novel of the same name, published in 1939. Through a theoretical and critical framework based on gender studies and men's studies - particularly the assumptions of Raewyn Connell (2005), Michael Kimmel (1998) and Eve Kosofsky Sedgwick (1985), we intend to analyze the way in which the character Harry Wilbourne dramatizes and performs a masculinity that move away from the hegemonic perimeter, thus making it possible to question predetermined and evaluative parameters of masculinity in the social dynamics of genders.
Keywords: Gender; Masculinities; The wild palms; William Faulkner